Application of a Dielectric Barrier Discharge Atmospheric Cold Plasma (Dbd‐Acp) for Eshcerichia Coli Inactivation in Apple Juice - Liao, Xinyu; Li, Jiao; Muhammad, Aliyu Idris; Suo, Yuanjie; Chen, Shiguo; Ye, Xingqian; Liu, Donghong; Ding, Tian (Journal of food science, 2018)
Atmospheric cold plasma (ACP) is a promising non‐thermal technology in food industry. In this study, a dielectric barrier discharge (DBD)‐ACP exhibited strong bactericidal effect on Escherichia coli in apple juice. Under a 30 to 50 W input power, less than 40 s treatment time was required for DBD‐ACP to result in 3.98 to 4.34 log CFU/mL reduction of E. coli in apple juice. The inactivation behavior of ACP on E. coli was well described by the Weibull model. During the treatment, the cell membrane of E. coli was damaged severely by active species produced by plasma, such as hydrogen peroxide, ozone and nitrate. In addition, the ACP exposure had slight effect on the °Brix, pH, titratable acidity (TA), color values, total phenolic content, and antioxidant capacity of apple juice. However, higher level of DBD‐ACP treatment, 50 W for more than 10 s in this case, resulted in significant change of the pH, TA, color and total phenolic content of apple juice. The results in this study have provided insight in potential use of DBD‐ACP as an alternative to thermal processing for fruit juices in food industry. Practical Application Escherichia coli O157:H7 in apple juice is a potential risk for public health. This study demonstrated that 30 s cold plasma treatment resulted in more than 4 log CFU/mL reduction under 50 W, while the quality attributes of apple juice were not significantly affected. Therefore, cold plasma technology is a promising alternative substitute of traditional thermal processing for juice pasteurization.